Perbankan Syariah di Indonesia: Kajian Kritis atas Legislasi dan Implementasinya - Rasji; Muhammad Wildan Ichsandi (CV Rewang Rencang, 2024)
This study aims to analyze the implementation of legal politics in the development of Islamic banking in Indonesia and its contribution to the national economy. The method used is a normative juridical approach through statutory analysis and the progressive legal theory framework. The discussion shows that Islamic banking regulation in Indonesia evolved from Law No. 7 of 1992 to Law No. 21 of 2008, reflecting official recognition of a sharia-based financial system. Although legal frameworks exist, implementation faces philosophical (transparency), sociological (social stigma and HR), and juridical (technical gaps) challenges. Through the lens of progressive legal theory, Islamic banking law is seen not only as normative but also transformative for achieving social justice. Islamic banks play a crucial role in economic redistribution and empowering marginalized communities through ethical financing schemes. Regulatory synergy, public education, and institutional strengthening are essential to ensure the realization of substantive justice in practice. In conclusion, strengthening Islamic banking as a tool of social transformation requires adaptive regulation and consistent enforcement to support a just, inclusive, and sustainable national economic system.